Isolation, identification, and characterization of keratinase enzyme producing bacteria, collected from tannery soil - Tahmid, Md. Izhar; Siddiqua, Iritra (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.